Effect of Glycolic Acid Ethoxylate Lauryl Ether (GAL) Surfactant Solutions among Low and High Concentrations on Drag Reduction to Progress Flow in the Pipeline Networks Using RDA - Alsaedi, Sajda S.; Yousif, Zainab; Alazzawi, Sheymaa; Filip, Peter (Journal of Petroleum Research and Studies, 2022)
In the pipeline networks field, GAL surfactant can reduce drag forces relatively using a small quantity part per million (ppm). Accordingly, the drag reduction (DR) enhancement is highly recommended in many industrial applications specifically the crude oil transportation aspect. GAL solution was experimentally investigated at various concentrations. The experiments were performed at low concentrations range from 50 to 300 ppm, and high concentrations range from 1000 to 2000 ppm. The rotating disk apparatus (RDA) was used at various speeds range from 50 to 3000 rpm in all experiments. Torque values of the GAL solutions were compared with water alone. The results clearly show that the different concentrations of the Glycolic Acid Ethoxylate Lauryl Ether (GAL) are good drag reduction agents (DRAs), with clear and high torque reading differences. Further, GAL solutions have the same tendency at all concentrations. The torque finding was enhanced with increasing concentration.